Penerapan Media Pembelajaran Berbasis Aplikasi Blooket terhadap Mata Pelajaran PAI di SMA Nurul Amal Palembang - Ayu Rahmadhani Putri; Muhammad Fauzi; M. Robbani (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2025)
The background of this research is that there are still low learning outcomes in students because teachers only explain the material using the same learning methods and media. The purpose of this study is to find out whether there is an influence in the application of Blooket Application-basedlearning media on PAI subjects at SMA Nurul Amal Palembang. This research was conducted using a quantitative research design using the One Group Pretest Posttest research design. Based on the results of the study, the researcher grouped the learning outcomes into three groups, namely high, medium and low. From the results of the research, there is a significant difference in student learning outcomes, this is evidenced by the percentage of final grades where initially there were 5 students who got very low scores, but after being implemented there were only 3 students who had low scores.